광섬유격자센서와 회전광학커플러를 사용한 새로운 회전축의 토크 측정방법 - 황요하; 이종민 (한국소음진동공학회, 2007)
Torque of a rotating shaft has been mostly measured by strain gages combined with either a slip ring or telemetry. However, these methods have severe inherent problems like low S/N ratio, high cost, limited number of channels and difficult installation. In this paper, a new method using FBG(fiber bragg grating) sensors and a rotary optical coupler for online non-contact torque monitoring is suggested. FBG sensor can measure both strain and temperature, and has much batter characteristics than those of a strain gage. A rotary optical coupler is a optical connecting device between a rotating shaft and stationary side without any physical contact. It has been devised for transmitting light between a rotating optical fiber and a stationary optical fiber. The proposed method uses this rotary optical coupler to connect FBG sensors on the rotating shaft to instruments at stationary side. And a reference FBG sensor is also applied to compensate the insertion loss change of the rotary optical coupler due to rotation. Three FBG sensors have been fabricated in a single optical fiber. Two FBG sensors are attached on the shaft surface to measure torque and one sensor is installed at the shaft center to compensate the insertion loss change. The torque of a rotating shaft has been successfully measured by the suggested method proving its superior performance potential.